2016
DOI: 10.1534/genetics.116.190678
|View full text |Cite
|
Sign up to set email alerts
|

Effector-Triggered Immune Response in Arabidopsis thaliana Is a Quantitative Trait

Abstract: We identified loci responsible for natural variation in Arabidopsis thaliana (Arabidopsis) responses to a bacterial pathogen virulence factor, HopAM1. HopAM1 is a type III effector protein secreted by the virulent Pseudomonas syringae strain Pto DC3000. Delivery of HopAM1 from disarmed Pseudomonas strains leads to local cell death, meristem chlorosis, or both, with varying intensities in different Arabidopsis accessions. These phenotypes are not associated with differences in bacterial growth restriction. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 119 publications
(168 reference statements)
1
27
0
1
Order By: Relevance
“…Therefore, HopAM1 recognition in Xan‐2 and Xan‐5 seems to be involved in a weak ETI‐like response. A quantitative nature of the cell death response after HopAM1 bacterial delivery was recently reported in 98 Arabidopsis accessions (Iakovidis et al ., ). However, even though deletion of hopAM1 slightly increased bacterial growth in strong ETI‐like accession Bur‐0 (an accession evaluated in our screen that, unlike Xan‐2 and Xan‐5, was susceptible to Pst DC3000 infection), no correlation was found between the accelerated cell death response and disease resistance, as the same effect of increased bacterial growth for a strain lacking hopAM1 was observed after infection of both Col‐0 and Bur‐0 (Iakovidis et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, HopAM1 recognition in Xan‐2 and Xan‐5 seems to be involved in a weak ETI‐like response. A quantitative nature of the cell death response after HopAM1 bacterial delivery was recently reported in 98 Arabidopsis accessions (Iakovidis et al ., ). However, even though deletion of hopAM1 slightly increased bacterial growth in strong ETI‐like accession Bur‐0 (an accession evaluated in our screen that, unlike Xan‐2 and Xan‐5, was susceptible to Pst DC3000 infection), no correlation was found between the accelerated cell death response and disease resistance, as the same effect of increased bacterial growth for a strain lacking hopAM1 was observed after infection of both Col‐0 and Bur‐0 (Iakovidis et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Pto DC3000 containing HopBA1 is still growth restricted on Col-0, indicating a decoupling of cell death and disease resistance. Decoupling of cell death and disease resistance has been previously reported (47)(48)(49). HopBA1 is not present naturally in Pto DC3000, so better understanding its contribution to disease resistance might require future studies in its endogenous strains (P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…ETI has long been considered a monogenic trait in model species, a notion recently challenged by Iakovidis et al. (). These authors showed that cell death in 98 accessions of Arabidopsis in the response to a Pseudomonas syringae effector has a quantitative nature, exhibiting variation in timing of appearance and strength of the response.…”
Section: Discussionmentioning
confidence: 99%